Safety and treatment completion of latent tuberculosis infection treatment in the elderly population—A prospective observational study in Taiwan. (July 2020) - Feng, Jia-Yih; Huang, Wei-Chang; Lin, Shu-Min; Wang, Tsai-Yu; Lee, Susan Shin-jung; Shu, Chin-Chung; Pan, Sheng-Wei; Chen, Chung-Yu; Lin, Chih-Bin; Wei, Yu-Feng; Tung, Chin-Lien; Li, Chiao-Ping; et al.
Highlights: The occurrence of systemic adverse reactions (SARs) was similar in the elderly (≥60 years old) and young (<60 years old) LTBI patients. Middle-age (35–59 years old), body mass index <23 kg/m 2, the 3HP regimen, and end-stage renal disease were independent factors related to SARs. Extremely old (≥80 years) LTBI patients had a higher treatment interruption rate, especially when they had SARs. Abstract: Background: The detection and treatment of latent tuberculosis infection (LTBI) is a key step in eliminating tuberculosis (TB), but information on safety and on treatment interruption in elderly LTBI patients remains limited. Methods: This multicenter prospective observational study included individuals with LTBI who underwent preventive therapy. Incidents of systemic adverse reactions (SARs) and treatment interruption rates in an elderly group (≥60 years old) and a young group (<60 years old) were analyzed. Results: A total of 406 LTBI patients, comprising 167 elderly and 239 young patients, were included in the analyses. The incidence of SARs was similar in the elderly group (18%) and the young group (15.1%). Being middle-aged (35–59 years), body mass index <23 kg/m 2, a regimen of 3 months of once-weekly rifapentine plus isoniazid, and end-stage renal disease were independent factors associated with SARs. The treatment interruption rate was similar between the elderly group (21.6%) and the young group (15.9%). LTBI patients aged ≥80 years with SARs had the highest risk of treatment interruption. Conclusions: The occurrence of SARs was similar in the elderly (≥60 years old) and young (<60 years old) LTBI patients receiving preventive therapy. Extremely old (≥80 years old) LTBI patients had a higher treatment interruption rate, especially when they had SARs.